Development of Physician-Pharmacist Collaborative Refill Clinic for Reducing the Oversupply and Costs of Medicine in Orthopaedic Outpatient Clinic, Naresuan University Hospital - Chomngamdee, Patthareeya; Sakunrag, Itsarawan; Maphanta, Sirada; Pannarong, Aucharanan; Chaibhuddanugul, Nattharut; Laoruengthana, Artit (Naresuan University Journal: Science and Technology (NUJST); Vol 30 No 2 (2022): April-June 2022, 2021)
Background: The number of patients with degenerative disorder of skeletal system in outpatient clinic is increasing, thus crowd of patients waiting for health care service is typically time consuming in every scale of public hospital. Hence, a Physician-Pharmacist Collaborative Refill Clinic (Refill Clinic) was implemented in the outpatient clinic of orthopaedic department, Naresuan University Hospital, and we aimed to evaluate the impact of this program on medication possession ratio (MPR) and medication cost saving.         Method: This study is prospective cohort study during one fiscal year. The physician screened and referred patients who had stable condition, and required for long-term medication to the Refill Clinic. The pharmacist reviewed patient’s medications profile and conducted medication reconciliation to assess patient’s adherence and drug-related problems, as well as determined medication ‘s quantity, and dispensed medications at the adequate quantity until the next refill date. All the adverse reactions were also monitored. The MPR and medication costs saving after attending the Refill Clinic were primary outcomes. MPR 0.9-1.1 is determined as appropriate supply. Results: Of 162 patients participating in the Refill Clinic, mean age was 59±12.6 years, and 69.7% were female. The patient who had an appropriate drug possession prior to join the Refill Clinic ranged from 6.7-50%. After implementing the Refill Clinic, the appropriate supply increased to the range of 35.0-100.0%. The Refill Clinic project can totally save 66,294 baht of drug costs. None of the patient experienced severe side effects from medication. Conclusion: The Refill Clinic could improve the MPR and reduce total budget of medication in the patient who has stable condition, and required for long-term medication. Keyword: Refill clinic, Medication possession ratio, Chronic disease, Drug cost, Orthopaedic